Valuasi Ekonomi Nilai Jasa Hutan: Sebuah Literature Review - Zulfia Memi Mayasari; Fadilah, Fadilah; Reflis, Reflis; Satria Putra Utama; Mustopa Ramdhon (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
Forests are terrestrial ecosystems that are mostly covered with trees and dominate almost the entire land surface of the earth. Forests play an important role in ecology, social, economic and environmental aspects. Forests are useful as producers of environmental goods and services. The benefits of forests as producers of goods such as wood, rattan, medicinal plants, fruit and so on are clearly visible and immediately felt. However, other benefits of forests as producers of services such as absorbing carbon, producing oxygen, regulating water management, preserving ecosystems, preventing erosion and others whose benefits can be felt but not seen sometimes receive less attention from policy makers because they are not felt directly. in economics. In fact, these indirect benefits greatly influence the quality of the environment and are very beneficial for humans and other living creatures. This article provides an overview of the indirect benefits of forests through a review of several literature. This literature review shows that the indirect benefits of forests, especially as carbon absorbers and oxygen producers, make the largest contribution to calculating the total economic value, so that policy makers need more attention in managing forests so that they remain sustainable.